Performance assessments of cascade refrigeration system with expander boosted subcooling - Önder Kaşka; Nehir Tokgoz (Case Studies in Thermal Engineering)
This study involves the application of an expander-boosted subcooling refrigeration system to improve the performance of the cascade refrigeration cycles. While previous research has focused on the role of internal heat exchangers, economizers, and ejectors, this work delves deeper into the potential of subcooling to significantly boost system efficiency. In recent years, mechanical subcooling has gained attention as a key strategy in the refrigeration and air conditioning sectors. The study proposes three system configurations: a booster in both the high- and low-temperature stages (2SB), a booster in the high-temperature stage only (HSB), and a booster in the low-temperature stage only (LSB).Performance comparisons were made between R290/R170, R717/R170, and R161/R41 refrigerant pairs, targeting both low- and ultra-low-temperature refrigeration applications. Optimum intermediate and dimensionless temperature values were identified for each refrigerant pair across varying evaporator conditions. Detailed analyses revealed that natural R290/R170 and R161/R41 offers superior COP at evaporator temperatures below −35 °C, while the performance gains were significant across all temperatures. Among the configurations, 2SB outperformed the others, with performance enhancement rates increasing as evaporator temperatures decreased. Among the refrigerant pairs analyzed in this study, R161/R41, R161/R170, and R290/R170 have demonstrated the highest performance for low-temperature and ultra-low-temperature cooling applications, respectively. The study demonstrated performance improvements of up to 20 % at low evaporator temperatures, underscoring the potential of this approach to revolutionize refrigeration efficiency.